Real-time audio interaction in serious games for music learning - Barbancho-Pérez, Isabel; Tardón-García, Lorenzo José; Barbancho-Pérez, Ana María (My University, 2016)
In this LBD, we present several Apps for playing while learning music or for learning music while playing. The core of all the games is based on the good performance of the real-time audio interaction algorithms developed by the ATIC group at Universidad de Ma ́laga (SPAIN).
Keywords: Música - Estudio y enseñanza - Aplicaciones informáticas; Audio Interaction; Music Learning; Serious Games